Comparing Blended and Online Learners’ Self-Efficacy, Self-Regulation, and Actual Learning in the context of Educational Technology - Zhang, Zhuo; Xu, Qian; Koehler, Adrie; Newby, Timothy (Online Learning, 2023)
In this quantitative comparative study, we explored the differences in technology integration self-efficacy, use of self-regulated learning strategies, and actual learning between preservice teachers enrolled in blended sections (n = 275) and online sections (n = 50) of the same introductory educational technology course. The results revealed that preservice teachers enrolled in the online format of the course reported a significantly higher level of using time management strategies, but a significantly lower level of employing help-seeking strategies compared to preservice teachers enrolled in the blended format of the course. However, no significant differences in technology integration self-efficacy and actual learning existed. Results offer insight for designing educational technology courses that align with the needs of both online and blended learners and preparing preservice teachers that likely will be responsible for facilitating blended and online learning with their own students.